Stateful characterization of resistive switching TiO2 with electron beam induced currents - Brian D. Hoskins (Nature Portfolio, 2017)
Oxide-based memristors hold promise for artificial neuromorphic computing, yet the detail of the switching mechanism—filament formation—remains largely unknown. Hoskins et al. provide nanoscale imaging of this process using electron beam induced current microscopy and relate it to resistive states.